Jellyfish age backwards : nature's secrets to longevity - Brendborg, Nicklas (Little, Brown and Company, 2023)
Blending together the most cutting-edge research and stories from habitats all over the world, a molecular biologist explores what nature has to teach us about aging, revealing life spans we cannot imagine and physiological gifts that feel closer to magic than reality.